Utilization of Sustainable Food Gardens (P2L) as an effort to improve household food security in Cijaku Village - Siti Widiati; Insan Fauzy; Audrey Aulia Hakim; Annisa Melati Priyanto Putri; Mochamad Rafli; Zahirah Anggrain; Silfi Pajah Qolipah; Nur Fitri Amalia; Yosephine natalia; Muhammad Naufal Azhar; M. Taqy Rouhillah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Food security is the condition of fulfilling food needs in terms of quantity and quality from household to national levels, and one way to meet these needs is through the application of Sustainable Food Gardens (P2L). Sustainable Food Gardens are crucial for enhancing food self-sufficiency, supporting food consumption diversification by cultivating various crops and raising livestock, optimizing land use in household gardens, and contributing to local economic strengthening through local production. The implementation of P2L enables communities to contribute to environmental sustainability in the agricultural sector. This service is conducted in Cijaku Village, Cijaku District, Lebak Regency, Banten Province. It utilizes qualitative descriptive methods by conducting socialization, assistance, focus group discussions, and evaluation. Empowering communities through Sustainable Food Utilization to support household food security involves various factors that support sustainability and food self-sufficiency at the local level. The results of the socialization showed that 48.14% of respondents did not know about the P2L program before, and 40.74% had never attended related training. After the socialization, 51.85% of the community understood that P2L could help family food security, and 59.26% started implementing P2L by planting green vegetables. Socialization is considered easy to do (48.14%) and well-delivered (51.85%). P2L can support food diversification, and sustainable land management, serve as an adaptation strategy to climate change, optimize water usage, empower women, increase household production, and enhance community involvement in meeting food needs independently.